(untitled) (Research, Society and Development, 2025)
The objective of this narrative review is to discuss the physiological mechanisms of preanesthetic stress in small animals, its main triggers, intra- and postoperative repercussions, and the most current mitigation strategies, highlighting knowledge gaps and prospects for standardizing protocols in different clinical settings. Preanesthetic stress in dogs and cats represents a significant challenge for clinical practice, as it interferes with hemodynamic stability, anesthetic pharmacodynamics, and animal welfare. This response is mediated by the hypothalamic-pituitary-adrenal axis and the sympathetic nervous system, resulting in physiological and behavioral changes that increase the risk of perioperative complications. The main stressors include transportation, clinical handling, and separation from the owner. Mitigation strategies include low-stress management techniques, environmental enrichment, and pharmacological interventions, such as the use of anxiolytics (gabapentin, pregabalin, and trazodone). Recent evidence suggests that stress reduction can reduce the need for anesthetics, improve postoperative recovery, and reduce complications. However, the heterogeneity of protocols reinforces the need for further studies to standardize effective approaches across different species and clinical settings.